Rapid and reproducible characterization of sickling during automated deoxygenation in sickle cell disease patients. Issue 5 (8th March 2019) - Rab, Minke A.E.; van Oirschot, Brigitte A.; Bos, Jennifer; Merkx, Tesy H.; van Wesel, Annet C.W.; Abdulmalik, Osheiza; Safo, Martin K.; Versluijs, Birgitta A.; Houwing, Maite E.; Cnossen, Marjon H.; Riedl, Jurgen; Schutgens, Roger E.G.; et al.
Abstract: In sickle cell disease (SCD), sickle hemoglobin (HbS) polymerizes upon deoxygenation, resulting in sickling of red blood cells (RBCs). These sickled RBCs have strongly reduced deformability, leading to vaso‐occlusive crises and chronic hemolytic anemia. To date, there are no reliable laboratory parameters or assays capable of predicting disease severity or monitoring treatment effects. We here report on the oxygenscan, a newly developed method to measure RBC deformability (expressed as Elongation Index ‐ EI) as a function of pO2 . Upon a standardized, 22 minute, automated cycle of deoxygenation (pO2 median 16 mmHg ± 0.17) and reoxygenation, a number of clinically relevant parameters are produced in a highly reproducible manner (coefficients of variation <5%). In particular, physiological modulators of oxygen affinity, such as, pH and 2, 3‐diphosphoglycerate showed a significant correlation (respectively R = ‑0.993 and R = 0.980) with Point of Sickling (PoS5% ), which is defined as the pO2 where a 5% decrease in EI is observed during deoxygenation. Furthermore, in vitro treatment with antisickling agents, including GBT440, which alter the oxygen affinity of hemoglobin, caused a reproducible left‐shift of the PoS, indicating improved deformability at lower oxygen tensions. When RBCs from 21 SCD patients were analyzed, we observed a significantly higher PoS in untreated homozygous SCD patients compared to treated patients and other genotypes. We conclude that the oxygenscan is a state‐of‐the‐art technique that allows for rapid analysis of sickling behavior in SCD patients. The method is promising for personalized treatment, development of new treatment strategies and could have potential in prediction of complications.